SIKAP ALUMNI PENDIDIKAN MASYARAKAT DALAM PENEMPATAN KERJA DENGAN KESESUAIAN BIDANG KEAHLIAN DAN BIDANG PEKERJAAN PADA PROGRAM STUDI PENDIDIKAN MASYARAKAT FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU - Mega Putri Anita; Jaspar Jas; Titi Maemunaty (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The study provides background for alumnus in job placement, so the problem with this study is whether or not the alumnus of public education in the presence of expertise and employment is already good? The merits of this research as an input and consideration material for the party. The study program as accredited and for enhanced insight and knowledge regarding attitudes in appropriate placement and disnatch the alumni educational background asa graduate of community education, so it can be successful and optimally this research is deskipctive with a quantitative approach,the population in this study is 60 alumnus, using the simple random sampling. Instruments in this study in an angket with 79 valid statement items to be fitted with research instrument, using an alternative answer on positive statement (SS) given a 4, ounce (S) weight 3 sometimes (cow) attached to 2, no ratter (P) on the weight of 1 and instead on statement negative results found alumnus research on job placement the skill and job matching that performance all right, this is proven by the recapitulation of the 3rd indicator, the highest achievement on the affective indicator with answer very often (SS) 75%.Key Words: Alumnus, Placement and Performance